PENERAPAN MEDIA AUDIOVISUAL BERMUATAN PLURIKULTURAL UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK PEMAHAMAN LINTAS BUDAYA PEMELAJAR BIPA - Effelina Zakkia Putri, Cindy; Vidya Asteria, Prima (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2026)
The purpose of this study was to describe the improvement of listening skills and cross-cultural understanding at level 5 after implementing pluricultural audiovisual media in the form of Indonesian cultural vlogs. This study used a single-group post-test design and a quantitative descriptive approach. Four level 5 BIPA learners from China, South Korea, and Malaysia at Surabaya State University became the research subjects; they were selected using a total sampling technique. Student Worksheets (LKM) with rubric-based listening skills assessment components and cultural reflection sheets based on Byram's (1997) Intercultural Communicative Competence (ICC) framework were used as research tools. Listening skills were analyzed using a one-sample t-test against the minimum competency criteria (KKM) of 70. The results showed that the average score of students' listening skills (M=86.5000) significantly exceeded the KKM of 70 (t=4.027; df=3; p<0.05). All learners had a high level of cross-cultural understanding, as evidenced by their ability to describe Indonesian socio-cultural customs (savoirs), decipher the cultural meaning of utterances in vlogs (savoir comprendre), and consider cultural differences honestly and empathetically (savoir être). It has been shown that pluricultural content in cultural vlogs that highlight diverse social practices from learners' different cultural backgrounds encourages more critical and thoughtful cross-cultural understanding. These results validate the effectiveness of implementing audiovisual media with pluricultural content as an authentic learning medium in supporting the simultaneous acquisition of linguistic and intercultural competencies in BIPA learners.